Support for Single Page Application Frameworks on FrameWeb - Hoppe, Pedro Henrique Brunoro; Souza, Vítor Estêvão Silva (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2023: Proceedings of the 29th Brazilian Symposium on Multimedia and the Web, 2023)
In the field of Web Engineering, many methods have been proposed to guide developers in designing and coding Web applications. The FrameWeb method is a model-driven approach that targets the development of systems that use certain kinds of frameworks in their architecture, proposing the use of models that incorporate concepts from these frameworks during design. Currently, the FrameWeb method does not consider SPA (Single Page Application) frameworks and, in recent years, they have gained a lot of popularity among developers. In this work, we propose to add support for SPA frameworks to FrameWeb. With our research, we have managed to update the FrameWeb meta-model so that its modeling language now supports SPA frameworks and their constructs. FrameWeb tools (graphical editor and code generator) also evolved to support the new elements. Experiments of modeling existing SPAs with this new version of FrameWeb, generating code from the models and comparing with the original, showed that, in average, around 69% of the HTML tags could be generated from the models. The support for SPA frameworks in FrameWeb allows developers to design and model their applications using constructs that relate to the frameworks used in practice, facilitating developer communication using the models and generating code to improve developer productivity.